DAMPAK PENERAPAN IFRS TERHADAP KUALITAS LAPORAN KEUANGAN DAN ARUS INVESTASI - Cahyati, Ari Dewi (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2018)
Objective of this study is to determine whether IFRS convergence will improve the quality of financial statements as indicated by decreasing levels of information asymmetry and declining real earnings management. IFRS convergence is measured by Dummy variables years before convergence and year after covergency while accounting quality reporting is measured by decreasing earnings management level and decreasing level of information asymmetry. Real earnings management uses abnormal cash flow, abnormal discretionary expense and abnormal production cost (Roydhuchory, 2006) while information asymmetry uses adjusted spreads. While the variable of investment flows is measured by the percentage of foreign investment ownership in Indonesia (defond et.al, 2011). This research uses a quantitative approach that aims to test the theory. The research method used is explanatory research. The sample of this study are all companies listed on BEI. Secondary data research data. From purposive sampling, 102 samples were obtained for IFRS convergence effect on Real earnings management and 100 companies to test the effect of IFRS convergence on asymmetry and information asymmetry on global investment flows. Methods of data analysis using linear regression analysis. The result of statistical analysis shows 1) that IFRS convergence has negative effect on real profit management. This indicates that the higher the IFRS convergence the real earnings management will decrease. 2) IFRS convergence has no effect on information asymmetry and 3) Information asymmetry has no effect on global investment flows in Indonesia.